2018
DOI: 10.1016/j.jpain.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Somatosensory Excitability Is Modulated in Response to Several Days of Muscle Soreness

Abstract: Changes in excitability of the sensorimotor cortex have been demonstrated in clinical musculoskeletal pain, although the timing is unknown. Eccentric exercise provokes delayed-onset muscle soreness providing a model to study the temporal profile of sensorimotor cortical plasticity during progressively developing muscle soreness. Twelve healthy participants performed eccentric exercise of the wrist extensors. Likert pain scores, pressure pain thresholds at the extensor carpi radialis (ECR) muscle, somatosensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Interestingly, when eccentric exercises were applied in NGF‐sensitized ECRB, such combined effect results in decreased cortical excitability that is most probably driven by neural protective mechanisms (De Martino, Zandalasini, et al, ). In addition, tonic infusion of hypertonic saline or muscle soreness induced by eccentric exercises in the upper limbs is also related with reduced corticomotor output (De Martino, Petrini, Schabrun, & Graven‐Nielsen, ; Le Pera et al, ; Schabrun, Burns, & Hodges, ). Therefore, it has been suggested that the inhibitory motor effects associated with prolonged nociceptive inputs can override the proclivity to short‐term increase in corticomotor excitability in already NGF‐sensitized muscles (De Martino, Zandalasini, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when eccentric exercises were applied in NGF‐sensitized ECRB, such combined effect results in decreased cortical excitability that is most probably driven by neural protective mechanisms (De Martino, Zandalasini, et al, ). In addition, tonic infusion of hypertonic saline or muscle soreness induced by eccentric exercises in the upper limbs is also related with reduced corticomotor output (De Martino, Petrini, Schabrun, & Graven‐Nielsen, ; Le Pera et al, ; Schabrun, Burns, & Hodges, ). Therefore, it has been suggested that the inhibitory motor effects associated with prolonged nociceptive inputs can override the proclivity to short‐term increase in corticomotor excitability in already NGF‐sensitized muscles (De Martino, Zandalasini, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Any change in pain threshold reflects, albeit indirectly and with some limitations, the change in sensitivity of group III/IV muscle afferents. Therefore, any change in pain pressure threshold can be used an indirect marker of change in sensitivity of group III/IV muscle afferents (Graven-Nielsen et al 2004 ; Schabrun et al 2016 ; De Martino et al 2018 ). Sensitivity of group III/IV muscle afferents was quantified by means of pain pressure threshold (PPT was assessed alternatively in both thighs (exercising vs non-exercising leg) after each cycle of occlusion during IP and SHAM treatment by a pressure algometer (Force Ten FDX 50, Wagner Instruments, Greenwich, CT).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have indicated that transcranial direct current stimulation (tDCS) and other transcranial stimulation methods, such as repetitive transcranial magnetic stimulation, can modulate musculoskeletal pain development in experimental settings [32,33] and yield pain relief in patients with fibromyalgia [34,35]. As patients with knee osteoarthritis often display impaired CPM compared with healthy participants [36], a recent study by Ahn et al [37 & ] assessed the modulatory effect of tDCS on CPM in patients with osteoarthritis.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%